Isolation and screening of potential microorganisms for citric acid production from sewage treatment plant sludge - Jamal, Parveen; Alam, Md. Zahangir; Mohd Salleh, Mohammad Ramlan; M. Akib, Munirah (2005)
The better utilization of sewage treatment (STP) sludge through value added products is being considered to be an alternative cost effective solution for waste management. The study emphasized on isolation of filamentous fungi especially Aspergillus from STP sludge for better adaptability. Liquid state fermentation process was used forthe production of citric acid. Six strains of Aspergillus niger (A-SS101, A-SS102, A-SS104, A-SS105, A-SS106 and A-SS-107) were isolated from STP sludge and identified using slide culture technique followed by image analysis. Four strains were screened under controlled fermentation conditions such as pH range of 2-3, temperature 30 degree celcius and agitation 150 rpm, using the substrate of STP sludge (1% of total suspended solids, TSS), 2% (w/v) co-substrate (wheat flour) with inoculum's size of 2% (10^8 spores/ml). Evaluation of fungal potentiality was done in terms of maximum citric acid production, biosolid production (TSS %) and removal of chemical oxygen demand (COD). Strain A-SS106 produced the highest concentration of citric acid (0.14 g/L), TSS (15.18 g/L) and COD removal (90.1%) followed by SC906, A-SS106, A1020 and A103 on fourth day of fermentation.